Gastric ulcerations after a traumatic horse kick - Danny Poon, MD; Iliya Goldberg, MD, MS; Ada Lee, DO; Lesley Small-Harary, MD; Erica Gross, MD (Elsevier, 2020)
Blunt abdominal trauma in pediatric patients can lead to a wide range of consequences and disease processes. To date, there have only been a few documented cases of gastric ulcers from blunt abdominal trauma. Even less frequent, are reports describing 'kissing gastric ulcers' from blunt abdominal injuries in the pediatric patient population. In our case report, we highlight a case of a 13-year-old female presenting to an emergency room after sustaining a kick to the abdomen by a horse. Initial cross sectional imaging was significant for mild left upper quadrant mesenteric edema and the patient was discharged in stable condition. However, upon repeat presentation to the emergency room with hematemesis, an upper endoscopy was performed revealing two large opposing areas of ulceration on the greater and lesser curvature of the stomach. This case report provides an insight in to a rare condition that can be difficult to diagnose. Clinicians must be cognizant of these potential injuries when evaluating patients presenting with blunt abdominal trauma.